1997
DOI: 10.1152/ajpheart.1997.273.3.h1126
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the human pulmonary vascular response to 8 hours of isocapnic hypoxia

Abstract: To examine the hypothesis that the human pulmonary vascular response to hypoxia has a component with a slow time course, we measured pulmonary vascular resistance (PVR) in six healthy adult males during 8 h of isocapnic hypoxia. A balloon-tipped pulmonary artery catheter with thermistor was introduced via a forearm vein and used to derive PVR. The subjects were seated in a chamber in which the oxygen and carbon dioxide concentrations were adjusted to maintain an end-tidal Po2 of 50 Torr and an end-tidal Pco2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 0 publications
10
82
1
Order By: Relevance
“…However, there was a progressive increase in heart rate with hypoxia, as has been previously reported Dorrington et al 1997). The present study found no effect of â-blockade on the progressive increase in heart rate with hypoxia, or on either of its underlying components (GHR and HR100%).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, there was a progressive increase in heart rate with hypoxia, as has been previously reported Dorrington et al 1997). The present study found no effect of â-blockade on the progressive increase in heart rate with hypoxia, or on either of its underlying components (GHR and HR100%).…”
Section: Discussionsupporting
confidence: 84%
“…We will therefore only consider the Doppler measurements of cardiac output further in this section. In a previous study (Dorrington et al 1997), a gradual increase in cardiac output was observed over an 8 h exposure to the same level of hypoxia as employed in the present study. From the raw data associated with the previous study, the rise in cardiac output between 1 and 8 h can be calculated as 0.98 l min¢ (95% confidence interval (CI) 0.36 to 1.34 l min¢, P < 0.05, one-sample t test).…”
Section: Cardiac Outputsupporting
confidence: 75%
See 1 more Smart Citation
“…This is most likely due to the slower onset of strong hypoxia in spontaneously breathing mice kept in 10% O 2 . A similar time course for the development of HPV has been also reported for humans (17). The specificity of the elevation of AEA was further demonstrated by 2-AG measurements that displayed no change upon hypoxia exposure (n ≥ 5, *P > 0.05 for 0 h vs. 1, 2, 6, and 24 h).…”
Section: Aea-induced Pulmonary Vasoconstriction Is Mediated By Faah-dsupporting
confidence: 77%
“…72,73 HPV arises acutely upon exposure to hypoxia, with a significant increase in pulmonary vascular resistance (PVR) within 30 minutes and, if the hypoxic exposure remains brief (minutes to a few hours), largely reverses rapidly with return to normoxia. 74 The onset of HPV occurs in phases, with an initial phase occurring within 5 minutes that reflects Ca 2+ -dependent smooth muscle contraction and a later phase of increasing PA pressure that appears to be Ca 2+ independent. 73 The initial hypoxic increase in intracellular Ca 2+ in PASMCs is mediated by Ca 2+ release from the sarcoplasmic reticulum and Ca 2+ entry through voltage-gated L-type Ca 2+ channels, Ca 2+ permeable nonselective cation channels, and receptor-operated Ca 2+ channels; in addition, hypoxia increases the sensitivity of the myofilament contractile apparatus to Ca 2+ .…”
Section: Role Of Nhe1 In Acute Hypoxic Pulmonary Vasoconstriction (Hpv)mentioning
confidence: 99%